Financial Behavior of Engineering Productions in the Face of Economic Sanctions (in Novosibirsk Region) - L. I. Lugacheva; M. M. Musatova; T. S. Soboleva (Мир новой экономики)
The article considers the financial situation of the mosaic of regional machine-building complex of the Novosibirsk Region (NSR) in the period of economic sanctions for Russia. The article deals with the financial behavior and strategies of machine-building enterprises of the Novosibirsk region. The article covers the topic of the study of statistical data on the financial status of machine-building enterprises of the region. The authors identify the main issues and areas of sustainable development of regional financial engineering in the conditions of economic blockade. In the work carried out is the processing of statistical data that allowed to give the quantitative characteristics of the performance of the machine-building enterprises of the region under the conditions of sanctions. The study used the methods of analysis, synthesis, integrated approaches, comparisons, and other methods of systematic knowledge. The authors made conclusions about the reasons that caused the difficult financial situation of the machine-building enterprises in recent years, and the need for enhanced cooperation of business and government in the framework of the policy of import substitution and economic security.